Tingkat Pemahaman Generasi Z Terhadap Investasi Saham Syariah Pada Mahasiswa yang Tergabung dalam Organisasi Forum Silaturahim Studi Ekonomi Islam (FOSSEI) - Saepudin, Asep; Prahara, Rahma Sandhi; Khopipah, Tsania Siti (Innovative: Journal Of Social Science Research, 2024)
Abstract With the digitalization system among the current generation of students, namely Generation Z students, education and the use of investment in the Sharia capital market have become easily accessible and understandable. To support education for the public or students, the Indonesia Stock Exchange (IDX) also conducts periodic education and socialization programs that can be accessed by various groups. The purpose of this research is to exctend the level of understanding of Generation Z students regarding Shariah stock investment. In this research, the author used a quantitative research method with a survey approach. The data type in this study is primary data on Shariah stock investment. The sample size in this study was 380 respondents. Data analysis in this study used descriptive statistical analysis. The research result indicated that the level of understanding of generation Z students of members the FoSSEI organization fall into the category of very high, indicating that the cooperation between FoSSEI and IDX in increasing students' literacy towards the Shariah capital market can be considered successful. Keyword: FOSSEY, Generation Z, Investment, Sharia, Stock